Visual Simulation and Case Inversion of Gas Explosion in Underground Mine - Qiu Jinwei; Jiang Bingyou; Tang Mingyun; Zhou Liang; Ren Bo; Yang Yingdi (Advances in Civil Engineering)
To truly represent the developing changes and spatiotemporal effects of gas explosion in underground mine, this paper discussed the field modeling and visual simulation technology of mine gas explosion. Through analyzing the characteristics of various field parameters, space geometric field models, physical attribute field models, and meteorological parameter field models were established to describe mine engineering, ventilation network, and explosion disaster process, respectively. Based on the generated model class and simulation timing flow of gas explosion disaster field, OpenGL technology was adopted to visualize the model of gas explosion disaster field, which simulated the overpressure propagation process of gas explosion shockwave and dynamic spread process of disaster gas, thereby to reveal the developing changes of gas explosion parameters in time and space. Taking the gas explosion accident that occurred in a certain mine in China as an example, the disaster process was inferred to examine the availability of the mine gas explosion disaster field model. The research achievements in the paper not only embody the great engineering value of visual simulation technology in the field of safety engineering but also provide references for accident impact prediction, assessment, and emergency plan.